Polypropylene film, vapor-deposited polypropylene film and laminated film
By adopting a double-layer structure in the polypropylene film and adjusting the characteristics of the resistor, the problem of surface damage during use of the polypropylene film is solved, and higher scratch durability and atomization resistance are achieved, which is suitable for evaporation and printing treatments.
Patent Information
- Application Number
- JP2024175272
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-10-04
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-10-04
AI Technical Summary
The existing polypropylene films are prone to surface clouds due to surface damage during winding and use, reducing the value of printing design and product.
A polypropylene film with a double-layer structure is adopted, wherein both the first and second surface layers contain resistors, and a specific scratch durability formula is satisfied by adjusting the average particle size, pore volume and surface roughness of the resistors.
It significantly improves the scratch durability and atomization resistance of the polypropylene film, prevents surface damage and design degradation, and is suitable for evaporation and printing treatments.
Smart Images

Figure 0007667367000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polypropylene film consisting of at least two layers, a first surface layer and a second surface layer, a vapor-deposited polypropylene film using the polypropylene film, and a laminate film using the vapor-deposited polypropylene film, and particularly to a polypropylene film, vapor-deposited polypropylene film, and laminate film that are suitable for vapor deposition and printing processing. [Background technology]
[0002] Generally, polypropylene films are wound into rolls after production, and are treated as necessary to provide functionality to the film surface by deposition processing, printing processing, etc. This type of polypropylene film is produced by adding an antiblocking agent such as silica particles to improve processability. However, by adding an antiblocking agent to the film, the film surface may be scratched when the films rub against each other during winding, etc. If deposition or printing is performed on a scratched film surface, the appearance may deteriorate, such as appearing cloudy, and the design may be reduced. In addition, even in a vapor-deposited film that has been vapor-deposited, the surface of the vapor-deposited layer may be scratched when the films rub against each other during winding, etc., and the design may be reduced. Furthermore, the printed surface may be scratched when the films rub against each other during winding, etc. during printing processing, and there is a concern that the design and product value may be reduced.
[0003] As a technique for imparting scratch resistance to the film surface of this type of film, it has been proposed to adjust the average particle size, pore volume, etc. of the antiblocking agent to a predetermined value (see, for example, Patent Document 1). However, with this film, as the amount of antiblocking agent added increases, the roughness of the film surface increases, making it difficult to prevent scratches on the deposition surface.
[0004] Also, films have been proposed in which the amount of antiblocking agent on the printed surface is reduced to provide printability, and the amount of antiblocking agent on the non-printed surface is increased to provide blocking resistance, such as a film in which the amount of amorphous silica added to the printed surface layer is less than the amount of amorphous silica added to the non-printed surface layer (see Patent Document 2) and a film in which the amount of crystalline silica added to the printed surface layer is less than the amount of amorphous silica added to the non-printed surface, so that the average roughness of the printed surface layer is less than the average roughness of the non-printed surface layer (see Patent Document 3). However, with this film, when the printed surface and the non-printed surface rub against each other during winding, etc., it is difficult to prevent the printed surface from being scratched. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2004-076004 A [Patent Document 2] JP 2020-151907 A [Patent Document 3] JP 2016-196159 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made in consideration of the above-mentioned points, and provides a polypropylene film, a vapor-deposited polypropylene film, and a laminated film that have excellent scratch resistance on the film surface that is subjected to vapor deposition processing or printing processing. [Means for solving the problem]
[0007] That is, the first invention relates to a polypropylene film consisting of at least two layers, namely a first surface layer and a second surface layer, both of which contain an antiblocking agent, characterized in that the polypropylene film satisfies the scratch resistance value shown in the following formula (i) when the arithmetic mean roughness in the three-dimensional surface roughness of the first surface layer is SRa1 (μm) and the number of peaks with a height of 1 μm or more in the three-dimensional surface roughness of the second surface layer is SPc2 (pieces).
[0008]
number
[0009] The second invention relates to a polypropylene film according to the first invention, which satisfies the scratch resistance value shown in the following formula (ii) when the pore volume of the antiblocking agent contained in the second surface layer, determined by a nitrogen adsorption method, is V2 (ml / g).
[0010]
number
[0011] A third invention relates to the polypropylene film according to claim 1 or 2, wherein in the first or second invention, a vapor-deposited layer is formed on the first surface layer by vapor deposition.
[0012] A fourth invention relates to the polypropylene film according to the first or second invention, wherein the first surface layer has a glossiness of 110% or more as measured in accordance with JIS Z 8741 (1997).
[0013] A fifth invention relates to the polypropylene film according to the first or second invention, wherein the first surface layer is subjected to a surface treatment.
[0014] A sixth invention relates to the polypropylene film according to the first or second invention, wherein the polypropylene film is a non-stretched film.
[0015] The seventh invention relates to a polypropylene film according to the first or second invention, wherein the antiblocking agent contained in the first surface layer has a pore volume of 0.5 to 1.3 ml / g as determined by a nitrogen adsorption method and an average particle size of 2.5 to 4.5 μm as measured by a laser diffraction method.
[0016] The eighth invention relates to a vapor-deposited polypropylene film consisting of at least two layers, a first surface layer and a second surface layer, both of which contain an antiblocking agent, in which a vapor-deposited layer is formed on the first surface layer, characterized in that the vapor-deposited polypropylene film satisfies the scratch resistance value given by the following formula (iii) when the arithmetic mean height of the vapor-deposited layer is Sa1 (μm) and the number of peaks in the three-dimensional surface roughness of the second surface layer that have a peak height of 1 μm or more is SPc2 (numbers).
[0017]
number
[0018] The ninth invention relates to the vapor-deposited polypropylene film according to claim 7, which satisfies the scratch resistance value shown in the following formula (iv) when the pore volume of the antiblocking agent contained in the second surface layer, determined by a nitrogen adsorption method, is V2 (ml / g).
[0019]
number
[0020] A tenth aspect of the present invention relates to the vapor-deposited polypropylene film according to the eighth or ninth aspect of the present invention, wherein the gloss of the vapor-deposited layer measured in accordance with JIS Z 8741 (1997) is 720% or more.
[0021] An eleventh invention relates to the vapor-deposited polypropylene film according to claim 8 or 9, in the eighth or ninth invention, wherein the polypropylene film is a non-oriented film.
[0022] A twelfth invention relates to a vapor-deposited polypropylene film according to the eighth or ninth invention, wherein the antiblocking agent contained in the first surface layer has a pore volume of 0.5 to 1.3 ml / g as determined by a nitrogen adsorption method, and an average particle size of 2.5 to 4.5 μm as measured by a laser diffraction method.
[0023] The thirteenth invention relates to a laminate film using the vapor-deposited polypropylene film of the eighth or ninth invention, characterized in that at least one layer of lamination base film made of any one of a polyester-based film, a polyamide-based film, and a polypropylene-based film is laminated on the vapor-deposited layer side of the vapor-deposited polypropylene film. Effect of the Invention
[0024] According to the first aspect of the present invention, the polypropylene film is composed of at least two layers, a first surface layer and a second surface layer, and both of the first surface layer and the second surface layer contain an antiblocking agent. When the arithmetic mean roughness in the three-dimensional surface roughness of the first surface layer is SRa1 (μm) and the number of peaks having a height of 1 μm or more in the three-dimensional surface roughness of the second surface layer is SPc2 (pieces), the scratch resistance value shown in the above formula (i) is satisfied. Therefore, the film has excellent scratch resistance and good scratch haze, and scratches on the first surface layer are reduced, thereby suppressing deterioration of appearance when subjected to deposition, printing, etc., and the film can be suitably used as a base film for deposition or a film for printing.
[0025] According to the polypropylene film of the second invention, when the pore volume of the antiblocking agent contained in the second surface layer in the first invention is V2 (ml / g) as determined by a nitrogen adsorption method, the value of the scratch resistance represented by the above formula (ii) is satisfied. Therefore, scratches on the first surface layer are further reduced, and deterioration of appearance when vapor deposition, printing, or the like is performed can be suppressed.
[0026] According to the polypropylene film of the third invention, in the first or second invention, a vapor-deposited layer is formed on the first surface layer by vapor deposition, and therefore the vapor-deposited layer is formed on the first surface layer which is less susceptible to scratches, resulting in excellent design properties when made into a vapor-deposited film.
[0027] According to the polypropylene film of the fourth invention, in the first or second invention, the glossiness of the first surface layer measured in accordance with JIS Z 8741 (1997) is 110% or more, and therefore the polypropylene film has excellent glossiness and a luxurious appearance.
[0028] According to the polypropylene film of the fifth invention, in the first or second invention, the first surface layer is subjected to a surface treatment, so that the adhesion between the polypropylene film and the vapor deposition can be improved.
[0029] According to the polypropylene film of the sixth invention, in the first or second invention, the polypropylene film is a non-stretched film, so that whitening is unlikely to occur and the heat seal strength is high.
[0030] According to the polypropylene film of the seventh invention, in the first or second invention, the pore volume of the antiblocking agent contained in the first surface layer is 0.5-1.3 ml / g as determined by the nitrogen adsorption method, and the average particle size is 2.5-4.5 μm as measured by the laser diffraction method, so that the film has excellent scratch resistance and good scratch total light transmittance, and when the deposition layer is formed, scratches on the deposition layer are reduced, and deterioration of the design of the film due to rubbing between films can be suppressed. In addition, cracks in the deposition layer are reduced, and deterioration of the barrier property can be prevented.
[0031] The eighth aspect of the present invention provides a vapor-deposited polypropylene film which is a polypropylene film consisting of at least two layers, a first surface layer and a second surface layer, both of which contain an antiblocking agent, and in which a vapor-deposited layer is formed on the first surface layer. When the arithmetic mean height of the vapor-deposited layer is Sa1 (μm) and the number of peaks in the three-dimensional surface roughness of the second surface layer which have a peak height of 1 μm or more is SPc2 (pieces), the vapor-deposited polypropylene film satisfies the scratch resistance value shown in the following formula (iii). Therefore, the film has excellent scratch resistance and good scratch haze, and scratches in the vapor-deposited layer are reduced, thereby preventing deterioration in appearance.
[0032] In the vapor-deposited polypropylene film of the eighth invention, when the pore volume of the antiblocking agent contained in the second surface layer, determined by the nitrogen adsorption method, is V2 (ml / g), the film satisfies the scratch resistance value shown in the above formula (iv), so scratches on the vapor-deposited layer are further reduced, and deterioration of appearance can be suppressed.
[0033] According to the vapor-deposited polypropylene film of the tenth invention, in the eighth or ninth invention, the gloss of the vapor-deposited layer measured in accordance with JIS Z 8741 (1997) is 720% or more, and therefore the film has excellent gloss and a luxurious appearance.
[0034] According to the vapor-deposited polypropylene film of the eleventh invention, in the eighth or ninth invention, the polypropylene film is a non-stretched film, and therefore has excellent suitability as a vapor-deposited film.
[0035] According to the twelfth aspect of the present invention, in the vapor-deposited polypropylene film of the eighth or ninth aspect, the antiblocking agent contained in the first surface layer has a pore volume of 0.5 to 1.3 ml / g as determined by the nitrogen adsorption method and an average particle size of 2.5 to 4.5 μm as measured by the laser diffraction method, so that the film has excellent scratch resistance and good scratch total light transmittance, and scratches on the vapor-deposited layer are reduced, thereby preventing deterioration of the design of the film due to rubbing between films. In addition, cracks in the vapor-deposited layer are reduced, preventing deterioration of the barrier properties.
[0036] The laminate film according to the thirteenth aspect of the present invention is a laminate film using the vapor-deposited polypropylene film of the eighth or ninth aspect of the present invention, and has at least one layer of lamination base film made of any one of a polyester-based film, a polyamide-based film, and a polypropylene-based film laminated on the vapor-deposited layer side of the vapor-deposited polypropylene film. This makes it possible to form a laminate film that can suppress deterioration of the vapor-deposited layer, and can be suitably used as various packaging bags, etc. [Brief description of the drawings]
[0037] [Figure 1] FIG. 1 is a schematic cross-sectional view of a polypropylene film according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view of a vapor-deposited polypropylene film according to one embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic cross-sectional view of a laminated film using a vapor-deposited polypropylene film according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0038] The polypropylene film 10 according to one embodiment of the present invention shown in FIG. 1 is composed of at least two layers, a first surface layer 20 and a second surface layer 30, and both the first surface layer 20 and the second surface layer 30 are configured to contain an antiblocking agent. This polypropylene film 10 is preferably used as a deposition film, in which deposition processing or printing processing is performed mainly on one side. In addition, when the polypropylene film 10 is used as a deposition film, it is preferable that it is a non-stretched film. In the non-stretched film, stretching is suppressed and the orientation of the film is reduced, so that whitening is unlikely to occur and the heat seal strength is high. In addition, the non-stretched film also includes a case where unavoidable stretching is applied during film formation.
[0039] The polypropylene resin used as the resin raw material for the polypropylene film 10 is appropriately selected from resins produced from appropriate starting materials such as petroleum-derived, biomass-derived, material recycling-derived, and chemical recycling-derived. The type of polypropylene resin may be any general polypropylene resin, and may be selected from at least one of propylene homopolymer, propylene-α-olefin random copolymer such as propylene-ethylene random copolymer or propylene-ethylene-butene random copolymer, or propylene-ethylene block copolymer. In particular, it is preferable that the main component is a propylene-α-olefin random copolymer. The polypropylene resin may be a mixture of one or more of the above.
[0040] In the case of polypropylene resin, the melt flow rate (MFR) is not particularly limited. From the viewpoint of film moldability, the MFR of the polypropylene resin is preferably 1 to 20 g / 10 min, particularly 2 to 10 g / 10 min, measured at 230° C. and a load of 2.16 kg according to JIS K 7210. If the MFR of the polypropylene resin used is too low, the pressure of the extruder used for molding becomes excessively high, which tends to reduce productivity. If the MFR is too high, the melt viscosity of the resin becomes low, which makes it easy to break during molding, and film formation tends to be difficult.
[0041] The first surface layer 20 is a surface layer on one side of the polypropylene film 10 and contains an antiblocking agent. When used as a vapor-deposited film, the first surface layer 20 corresponds to a layer to be deposited having a vapor-deposited surface 21 on which vapor deposition is performed. When used as a printed film, the first surface layer 20 corresponds to a layer to be printed having a printed surface.
[0042] The second surface layer 30 is the other surface layer of the polypropylene film 10 and contains an antiblocking agent. The second surface layer 30 has a heat seal surface 31 that can be fused to an object by heat sealing when used as a vapor-deposited film.
[0043] The antiblocking agent is an additive for imparting blocking resistance and improving the processability of the polypropylene film 10. The type of antiblocking agent is not particularly limited, but for example, organic or inorganic particles or both are appropriately used. The organic particles can be obtained, for example, by emulsion polymerization or suspension polymerization, and examples thereof include polymethyl methacrylate, polystyrene, polyamide, etc. The inorganic particles can be, for example, silica, zeolite, talc, etc. These antiblocking agents may be used alone or in combination of two or more. From the viewpoint of the scratch resistance of the film, it is preferable to use inorganic particles such as silica or zeolite. The method of adding the antiblocking agent is not particularly limited, but it can be added by a known method, such as a method of preparing a high-concentration master batch and mixing it, or a method of mixing it by dry blending.
[0044] The amount of the antiblocking agent added to each of the surface layers 20 and 30 is not particularly limited. If the amount is too large, the cost increases, the film becomes less transparent, and the antiblocking agent is likely to fall off after film formation. If the amount is too small, the desired performance such as blocking resistance may not be obtained. For this reason, it is considered that the appropriate amount of the antiblocking agent to be added is, for example, 500 to 30,000 ppm, preferably 1,000 to 20,000 ppm.
[0045] In addition to the antiblocking agent, additives such as antioxidants, neutralizing agents, antistatic agents, antifogging agents, lubricants, nucleating agents, and colorants may be appropriately blended into the resin raw material constituting the polypropylene film 10 as necessary within a range that does not impair the object of the present invention. Among these additives, it is preferable to add a nucleating agent from the viewpoint of suitability for deposition processing. By blending a nucleating agent into the polypropylene resin, it is possible to promote the crystallization of the resin and improve the heat resistance, rigidity, and the like.
[0046] Examples of the nucleating agent that can be used include fatty acid metal salts, carboxylate metal salts, phosphoric acid ester metal salts, rosin metal salts, talc, mica, sorbitol derivatives, and high-density polyethylene resins. In particular, from the viewpoint of suitability for deposition, high-density polyethylene is more preferred. High-density polyethylene resins have a density of 0.945 to 0.975 g / cm. 3 is preferable, and 0.950 to 0.966 g / cm 3 If the density of the high-density polyethylene resin is too low, the crystallization rate may be low, and the heat resistance, etc. may be reduced. If the density of the high-density polyethylene resin is too high, the impact strength of the film may be reduced.
[0047] The polypropylene film 10 of the present invention may be composed of three or more layers including layers other than the first surface layer 20 and the second surface layer 30 as necessary. The polypropylene film 10 of FIG. 1 is a three-layer film having an intermediate layer 40 between the first surface layer 20 and the second surface layer 30. The intermediate layer 40 is mainly composed of polypropylene resin, and the polypropylene resin is selected from at least one of propylene homopolymer, propylene-α-olefin random copolymer such as propylene-ethylene random copolymer and propylene-ethylene-butene random copolymer, or propylene-ethylene block copolymer. In particular, it is preferable that the intermediate layer is mainly composed of propylene-α-olefin random copolymer. In addition to the polypropylene resin, a polyethylene resin may be added. By using a resin with any physical property for the intermediate layer 40, the film can be provided with appropriate functionality.
[0048] The thickness of the polypropylene film of the present invention is not particularly limited, but is appropriately determined according to demand, use, etc. For example, when deposition or printing processing is performed, 10 to 100 μm is preferable, and 15 to 70 μm is more preferable. If each surface layer 20, 30 is too thin, the antiblocking agent may fall off when the film passes through the roll during processing, and if it is too thick, the amount of antiblocking agent added may increase, resulting in poor visibility of the film. The thickness ratio of each layer of the polypropylene film is appropriately set, but whether it is two layers or three or more layers, it is composed of at least 10 to 85% of the first surface layer and 10 to 30% of the second surface layer. In particular, when it is composed of three layers, namely, the first surface layer, the intermediate layer, and the second surface layer, the thickness ratio is preferably 10 to 33.3% of the first surface layer, 33.4 to 80% of the intermediate layer, and 10 to 33.3% of the second surface layer.
[0049] The polypropylene film 10 of the present invention can be obtained by a known film forming method such as a T-die method or an inflation method. In particular, it is preferable to form the film by the T-die method. Film forming by the T-die method is advantageous in that it can provide high thickness and thinness precision required for a film. The polypropylene film 10 can also be used as a laminate (laminate film) in which other films are laminated. The method of laminating with other films is appropriately selected from known methods such as extrusion lamination and dry lamination.
[0050] In a polypropylene film having an antiblocking agent added to each surface layer, there is a concern that the film surface may be scratched when the films rub against each other due to the fine unevenness of the film surface. Therefore, in the polypropylene film 10 of the present invention, the first surface layer 20 is assumed to be the surface layer that is scratched and the second surface layer 30 is assumed to be the surface layer that scratches, and attention is paid to the arithmetic mean roughness in the three-dimensional surface roughness of the first surface layer 20 and the number of peaks with a height of 1 μm or more in the three-dimensional surface roughness of the second surface layer 30, and a correlation between the relationship between these parameters and scratch resistance is found, leading to an index of scratch resistance of the polypropylene film 10 having an antiblocking agent added to each surface layer 20, 30.
[0051] In other words, the polypropylene film 10 of the present invention satisfies the scratch resistance value shown in the following formula (i) when the arithmetic mean roughness of the three-dimensional surface roughness of the first surface layer 20 is SRa1 (μm) and the number of peaks with a height of 1 μm or more in the three-dimensional surface roughness of the second surface layer 30 is SPc2 (numbers).
[0052]
number
[0053] The arithmetic mean roughness (SRa1) in three-dimensional surface roughness is a parameter in the height direction, and is a value obtained by dividing the volume of the part surrounded by the roughness curved surface and the center surface by the measurement range, with the X and Y axes of the orthogonal coordinate system being placed on the center surface from the roughness curved surface, and the Z axis being the axis perpendicular to the center surface. The larger the arithmetic mean roughness in three-dimensional surface roughness, the rougher the film surface is, and the film surface on the surface layer on the side that is scratched tends to be less susceptible to scratching. In the polypropylene film 10, the first surface layer 20 is the surface layer on the side that is scratched, so the arithmetic mean roughness SRa1 (μm) in the three-dimensional surface roughness of the first surface layer 20 is an index of the resistance of the surface of the first surface layer 20 to scratching, and it can be said that the larger the value of the arithmetic mean roughness SRa1, the more the scratch resistance of the polypropylene film tends to improve.
[0054] The number of peaks (SPc2) with a peak height of 1 μm or more in the three-dimensional surface roughness is a parameter that indicates the degree of unevenness of the surface layer. In the surface layer on the scratching side, peaks with a height of a predetermined value (1 μm) or more are considered to be likely to scratch the surface of the opposing film that rubs against it, and the more the number of peaks, the more likely the opposing film surface is to be scratched. In the polypropylene film 10, the second surface layer 30 is the surface layer on the scratching side, so the number of peaks SPc2 (pieces) with a peak height of 1 μm or more in the three-dimensional surface roughness of the second surface layer 30 is an index of the ease with which the second surface layer 30 scratches the surface of the opposing first surface layer 20, and it can be said that the smaller the number of peaks SPc2 with a peak height of 1 μm or more, the more the scratch resistance of the polypropylene film 10 tends to improve.
[0055] The left side of the formula (i) is the scratch resistance of the polypropylene film expressed using these two indexes. As will be seen from the examples described later, when the scratch resistance value represented by the formula (i) satisfies 2100 or less, the second surface layer 30 of the polypropylene film 10 is less likely to scratch the first surface layer 20.
[0056] In formula (i), the arithmetic mean roughness SRa1 of the three-dimensional surface roughness, which is an index of the scratch resistance of the surface of the first surface layer 20, is the denominator of formula (i), and therefore the smaller the arithmetic mean roughness SRa1, the higher the scratch resistance value, which indicates that the first surface layer 20 is smoothed and the first surface layer 20 is more likely to be scratched by the second surface layer 30. Therefore, the arithmetic mean roughness SRa1 of the first surface layer 20 is preferably 0.01 to 0.15 μm, more preferably 0.02 to 0.08 μm. If the arithmetic mean roughness SRa1 of the first surface layer 20 is too small, the first surface layer 20 may not be rough enough and may be easily scratched. If the arithmetic mean roughness SRa1 is too large, the first surface layer 20 may be too rough and may function poorly as a vapor deposition film.
[0057] The numerator of formula (i) uses the number of peaks SPc2 having a height of 1 μm or more, which is an index of the susceptibility to scratches by the second surface layer 30. The larger the value of the number of peaks SPc2 having a height of 1 μm or more, the larger the scratch resistance value, indicating that the second surface layer 30 is more likely to scratch the first surface layer 20.
[0058] The number of peaks SPc2 having a height of 1 μm or more in the three-dimensional surface roughness, which is an index of the height of the unevenness of the second surface layer 30, indicates that the more the number SPc2 having a height of 1 μm or more, the larger the molecular value, and the more likely it is to damage the first surface layer 20. Therefore, the number of peaks SPc2 having a height of 1 μm or more in the second surface layer 30 is preferably 3 to 200, more preferably 5 to 130. If the number SPc2 having a height of 1 μm or more is too small, the performance such as blocking resistance due to the anti-blocking agent may be insufficient. If the number SPc2 having a height of 1 μm or more is too large, the number of peaks may be excessive, and the first surface layer 20 may be easily damaged.
[0059] In addition, the pore volume (V2) of the antiblocking agent added to the second surface layer 30 can also be used to derive an index of the scratch resistance of the polypropylene film 10 containing the antiblocking agent in each surface layer 20, 30. The pore volume (V2) of the antiblocking agent is the volume of fine pores present in the antiblocking agent determined by a nitrogen adsorption method, and can be used as an index of the hardness of the antiblocking agent. The larger the pore volume value of the antiblocking agent, the softer the antiblocking agent is, and the less likely the film surface is to be scratched when the film surfaces rub against each other. Conversely, the smaller the pore volume value, the harder the antiblocking agent is, and the more likely the film surface is to be scratched. The antiblocking agent constitutes the ridges on the film surface that cause scratches on the other film that rubs against it on the scratching surface, so it is considered that the softer the antiblocking agent is, the less likely the other film is to be scratched. From this, it can be said that the pore volume V2 (ml / g) of the antiblocking agent added to the second surface layer 30 is also an indicator of the susceptibility of the second surface layer 30 to scratches, and that the larger the pore volume V2 of the antiblocking agent, the more improved the scratch resistance of the polypropylene film tends to be.
[0060] In other words, the polypropylene film 10 of the present invention satisfies the scratch resistance value shown in the following formula (ii) when SRa1 (μm) indicates the arithmetic mean roughness of the three-dimensional surface roughness of the first surface layer 20, SPc2 (number) indicates the number of peaks with a height of 1 μm or more in the three-dimensional surface roughness of the second surface layer 30, and V2 (ml / g) is the pore volume of the antiblocking agent contained in the second surface layer determined by a nitrogen adsorption method, thereby achieving a further reduction in scratching of the first surface layer.
[0061]
number
[0062] The numerator of formula (ii) uses the number of peaks with a height of 1 μm or more, SPc2, which is an index of the susceptibility to scratching by the second surface layer 30, and the pore volume V2 of the antiblocking agent, and is expressed as the relationship (SPc2 / V2). Since (SPc2 / V2) is used as the numerator of formula (ii), the larger this value is, the greater the scratch resistance value is, indicating that the second surface layer 30 will more easily scratch the first surface layer 20.
[0063] The number of peaks SPc2 having a height of 1 μm or more in the three-dimensional surface roughness, which is an index of the height of the unevenness of the second surface layer 30, has a relationship of (SPc2 / V2), and indicates that the value of (SPc2 / V2) increases as the number of peaks SPc2 having a height of 1 μm or more increases, making it easier to damage the first surface layer 20. Therefore, the number of peaks SPc2 having a height of 1 μm or more in the second surface layer 30 is preferably 3 to 200, more preferably 5 to 130. If the number of peaks SPc2 having a height of 1 μm or more is too small, the performance such as blocking resistance due to the anti-blocking agent may be insufficient. If the number of peaks SPc2 having a height of 1 μm or more is too large, the number of peaks may be excessive, making it easier to damage the first surface layer 20. In addition, it is preferable that the layer thickness and particle size of the antiblocking agent used in the second surface layer 30 are appropriately selected from the range of about 2 to 13 μm so that the number SPc2 of peaks having a height of 1 μm or more in the second surface layer 30 satisfies 3 to 200.
[0064] In addition, the pore volume V2, which is an index of the hardness of the antiblocking agent, has a relationship of (SPc2 / V2), and as the pore volume V2 increases, the value of (SPc2 / V2) decreases, indicating that the first surface layer 20 is less likely to be scratched. Therefore, the pore volume V2 of the antiblocking agent in the second surface layer 30 is preferably 0.4 to 2 ml / g, more preferably 0.5 to 1.5 ml / g. If the pore volume V2 of the antiblocking agent is too small, the antiblocking agent may be too hard and may easily scratch the first surface layer 20. If the pore volume V2 is too large, the dispersibility of the antiblocking agent may decrease.
[0065] The average particle size of the antiblocking agent measured by the laser diffraction method is set according to the layer thickness of each surface layer 20, 30 to which the antiblocking agent is added. The average particle size is a value measured by the laser diffraction method in accordance with JIS Z 8825-1. For example, when the surface layer is thin, an antiblocking agent having a relatively small average particle size is suitable, and an antiblocking agent having a relatively large particle size tends to be unsuitable. On the other hand, when the surface layer is thick, an antiblocking agent having a relatively large average particle size is suitable, and an antiblocking agent having a relatively small particle size tends to be unsuitable. Specifically, an antiblocking agent having an average particle size suitable for the layer thickness of the surface layer is appropriately selected from the range of 1 to 15 μm, preferably 1 to 13 μm. If the average particle size of the antiblocking agent used is too small, the antiblocking performance may be insufficient, and if the average particle size is too large, the antiblocking agent may easily fall off or the visibility may deteriorate.
[0066] The pore volume of the antiblocking agent added to the first surface layer 20 determined by the nitrogen adsorption method is preferably 0.5 to 1.3 ml / g, and the average particle size measured by the laser diffraction method is preferably 2.5 to 4.5 μm. If the average particle size of the antiblocking agent added to the first surface layer 20 is too large, the surface of the first surface layer 20 tends to be too rough, and the design of the deposited film may be reduced. If the average particle size is too small, the surface of the first surface layer 20 tends to be insufficiently rough, and the first surface layer 20 may be easily scratched. In addition, if the pore volume of the antiblocking agent added to the first surface layer 20 is too small, that is, if the antiblocking agent is too hard, the deposited layer may be easily cracked, and the barrier properties against oxygen, water vapor, etc. may be reduced. On the other hand, if the pore volume of the antiblocking agent added to the first surface layer 20 is too large, that is, if the antiblocking agent is too soft, the dispersibility of the antiblocking agent tends to decrease, and the design of the polypropylene film 10 may be deteriorated. By setting the pore volume of the antiblocking agent added to the first surface layer 20 by the nitrogen adsorption method to 0.5 to 1.3 ml / g and the average particle size measured by the laser diffraction method to 2.5 to 4.5 μm, the scratch resistance of the first surface layer is improved and the film can have excellent permeability. In addition, when the film is made into a vapor-deposited film, scratches on the vapor-deposited layer are reduced, and the deterioration of the design due to rubbing between the films is suppressed. Furthermore, cracks in the vapor-deposited layer can be reduced, and the deterioration of the barrier properties against oxygen, water vapor, etc. can be suppressed.
[0067] In the polypropylene film 10 of the present invention, scratch haze was used to evaluate scratch resistance. Scratch haze is an index showing the scratch resistance (scratch resistance) of the film surface when two films are rubbed together, and is a value calculated from the difference between the haze of the film after rubbing and the haze of the film before rubbing. Haze is an index showing the transparency of a film measured in accordance with JIS K 7136 (2000), and a lower value indicates better transparency.
[0068] The higher the scratch haze value, the more the film surface is scratched by rubbing and the more the transparency is impaired, and the lower the value, the less the film surface is scratched by rubbing and the less the transparency is impaired. When the polypropylene film 10 is used as a vapor deposition film, the lower the scratch haze is preferable. In the polypropylene film 10 of the present invention, the scratch haze is preferably 10% or less, more preferably 6.5% or less. If the scratch haze is too high, the scratch resistance of the film is insufficient, and when used as a vapor deposition film, the film may look cloudy, resulting in poor appearance. If the scratch haze is 10% or less, it can be said that scratches on the first surface layer 20 (vapor deposition surface 21) caused by rubbing are suppressed, and therefore the deterioration of the design of the film due to rubbing between films during transportation and processing can be suppressed.
[0069] In addition, in the polypropylene film 10, the gloss of the first surface layer 20 is preferably 110% or more. The gloss is an index showing the shine, glare, and degree of regular reflection of light on the film surface, and is measured in accordance with JIS Z 8741 (1997). In order to provide the polypropylene film with good scratch resistance, as described above, it is preferable that the arithmetic mean roughness (SRa1) of the first surface layer is large. However, when it is made into a vapor-deposited film, it is considered that a good gloss is preferable because it has a high designability, and it is required to suppress the arithmetic mean roughness (SRa1) of the first surface layer. Therefore, by making it into a film having a certain degree of scratch resistance and a good gloss, it is possible to obtain a polypropylene film that can provide a vapor-deposited film with a more luxurious appearance.
[0070] In order to broaden the range of applications of the polypropylene film 10, it is preferable to perform a surface treatment on the first surface layer 20 on the deposition surface 21 side. Examples of surface treatments include atmospheric pressure plasma treatment, flame treatment, and corona discharge treatment. By performing a surface treatment on the deposition surface 21, it is possible to improve the adhesion between the polypropylene film and the deposition.
[0071] 2 shows a vapor-deposited polypropylene film 50 according to one embodiment of the present invention. This vapor-deposited polypropylene film 50 is an example in which a polypropylene film 10 containing an antiblocking agent in the first surface layer 20 and the second surface layer 30 is used as the base film of the vapor-deposited film, and a vapor-deposited layer 60 is formed on the first surface layer 20 of the polypropylene film 10.
[0072] The deposition layer 60 is formed by deposition processing directly on the deposition surface 21 of the first surface layer 20 or via an anchor coat layer. Deposition on the deposition surface 21 can impart barrier properties against water vapor, oxygen, etc. to the polypropylene film 10. As the deposition method, known methods such as vacuum deposition, sputtering, and ion plating can be used.
[0073] As the material for deposition, an appropriate material such as a metal deposition layer or an inorganic oxide layer is selected. The metal deposition layer is a thin film layer made of known metals such as aluminum, gold, silver, copper, chromium, etc., and may be a thin film layer of oxides, sulfides, or nitrides of these metals. The metal deposition layer may be a single layer or a plurality of layers of two or more different types or the same type. The inorganic oxide layer is made of known inorganic oxides such as aluminum oxide, silicon oxide, magnesium fluoride, magnesium oxide, etc., and is a thin film layer using one or more types of inorganic oxides.
[0074] With a vapor-deposited polypropylene film, there is a concern that when the base film is wound up after vapor deposition, the fine irregularities on the film surface may cause the films to rub against each other and scratch the film surface, just as with a polypropylene film. Therefore, with regard to the vapor-deposited polypropylene film 50 of the present invention, the vapor-deposited layer 60 is assumed to be the surface layer that is scratched, and the second surface layer 30 is assumed to be the surface layer that scratches, and an index of scratch resistance for the vapor-deposited polypropylene film 50 was derived by focusing on the arithmetic mean height of the vapor-deposited layer and the number of peaks with a height of 1 μm or more in the three-dimensional surface roughness of the second surface layer 30.
[0075] In other words, the vapor-deposited polypropylene film of the present invention satisfies the scratch resistance value shown in the following formula (iii) when the arithmetic mean height of the vapor-deposited layer 60 is Sa1 (μm) and the number of peaks in the three-dimensional surface roughness of the second surface layer 30 that have a peak height of 1 μm or more is SPc2 (numbers).
[0076]
number
[0077] The arithmetic mean height (Sa1) of the vapor-deposited layer 60 is a parameter in the height direction, and is a value that represents the average of the absolute values of the differences in height from the average plane of each measurement point. Since the vapor-deposited layer 60 is the surface layer that is likely to be scratched, the arithmetic mean height Sa1 (μm) of the vapor-deposited layer 60 is an index of how difficult the surface of the vapor-deposited layer 60 is to be scratched, and it can be said that the larger the arithmetic mean height Sa1, the more the scratch resistance of the polypropylene film tends to improve.
[0078] The number SPc2 (number) of peaks having a height of 1 μm or more in the three-dimensional surface roughness of the second outer layer 30 is an index of the susceptibility of the second outer layer 30 to scratch the surface of the opposing vapor-deposited layer 60, as described above.
[0079] The left side of the formula (iii) is the scratch resistance of the vapor-deposited polypropylene film expressed using these two indexes. As will be seen from the examples described later, when the scratch resistance value represented by formula (iii) satisfies 130 or less, the vapor-deposited layer 60 of the vapor-deposited polypropylene film 50 is less likely to be scratched by the second surface layer 30.
[0080] In formula (iii), the arithmetic mean height Sa1, which is an index of the resistance of the surface of the deposition layer 60 to scratches, is the denominator of the left side of formula (iii), and therefore the smaller the arithmetic mean height Sa1, the higher the scratch resistance value, which indicates that the deposition layer 60 is smoothed and the deposition layer 60 is more likely to be scratched by the second surface layer 30. Therefore, the arithmetic mean height Sa1 of the deposition layer 60 is preferably 0.2 to 1.5 μm, more preferably 0.3 to 0.8 μm. If the arithmetic mean height Sa1 of the deposition layer 60 is too small, the deposition layer 60 may not be sufficiently rough and may be easily scratched. If the arithmetic mean height Sa1 is too large, the deposition layer 60 may be too rough and may function poorly as a deposition film.
[0081] The numerator on the left side of formula (iii) is the same as in formula (i) above. As a surface layer on the side that scratches the deposition layer 60, the number of peaks SPc2 having a height of 1 μm or more, which is an index of the susceptibility to scratches, is used as an index.
[0082] Furthermore, an index of the scratch resistance of the vapor-deposited layer 60 can also be derived from the pore volume (V2) of the antiblocking agent added to the second surface layer 30. When the arithmetic mean height of the vapor-deposited layer 60 is Sa1 (μm), the number of peaks with a height of 1 μm or more in the three-dimensional surface roughness of the second surface layer 30 is SPc2 (pieces), and the pore volume of the antiblocking agent contained in the second surface layer determined by a nitrogen adsorption method is V2 (ml / g), if the scratch resistance value shown in the following formula (iv) is satisfied, scratches on the vapor-deposited layer can be further suppressed, and deterioration of the appearance of the vapor-deposited polypropylene film can be prevented.
[0083]
number
[0084] The denominator on the left side of formula (vi) is the arithmetic mean height Sa1, which is an index of the resistance of the surface of the vapor-deposited layer 60 to being scratched, and is the same as formula (iii). The numerator on the left side of formula (iv) is the same as formula (ii) described above. The number of peaks SPc2 with a peak height of 1 μm or more, which is an index of the susceptibility to being scratched, is used as an index for the surface layer that scratches the vapor-deposited layer 60. As will be seen from the examples described later, when the scratch resistance value represented by formula (iv) satisfies 165 or less, the vapor-deposited layer 60 is less likely to be scratched by the second surface layer 30 of the vapor-deposited polypropylene film 50.
[0085] The pore volume of the antiblocking agent added to the first surface layer 20 determined by the nitrogen adsorption method is preferably 0.5 to 1.3 ml / g, and the average particle size measured by the laser diffraction method is preferably 2.5 to 4.5 μm. If the average particle size of the antiblocking agent added to the first surface layer 20 is too large, the surface of the first surface layer 20 tends to be too rough, and the surface of the deposition layer 60 becomes too rough, which may reduce the design of the deposition film. If the average particle size is too small, the surface of the first surface layer 20 tends to be insufficiently rough, and the surface of the deposition layer 60 also becomes insufficiently rough, which may cause the deposition layer 60 to be easily scratched. In addition, scratches on the deposition layer are reduced, and the design deterioration due to rubbing between films can be suppressed. Furthermore, if the pore volume of the antiblocking agent added to the first surface layer 20 is too small, that is, if the antiblocking agent is too hard, the deposition layer 60 tends to be easily cracked, which may cause a decrease in the barrier properties against oxygen, water vapor, etc. On the other hand, if the pore volume of the antiblocking agent added to the first surface layer 20 is too large, that is, if the antiblocking agent is too soft, the dispersibility of the antiblocking agent tends to decrease, and the design of the vapor-deposited polypropylene film 50 may be reduced. By setting the pore volume of the antiblocking agent added to the first surface layer 20 to 0.5-1.3 ml / g as determined by the nitrogen adsorption method and the average particle size measured by the laser diffraction method to 2.5-4.5 μm, the scratch resistance of the first surface layer is improved and the film can have excellent permeability. In addition, when the film is made into a vapor-deposited film, scratches on the vapor-deposited layer are reduced, and the deterioration of the design due to rubbing between films is suppressed. Furthermore, cracks in the vapor-deposited layer can be reduced, and the deterioration of the barrier properties against oxygen, water vapor, etc. can be suppressed.
[0086] In the vapor-deposited polypropylene film 50 of the present invention, scratch total light transmittance was used to evaluate scratch resistance. The scratch total light transmittance is an index showing the scratch resistance (scratch resistance) of the film surface when the films are rubbed together, and is a value calculated from the difference between the maximum total light transmittance of the film after rubbing and the maximum total light transmittance of the film before rubbing. The lower the scratch total light transmittance, the better the light transmittance after rubbing, and it is preferable that the scratch total light transmittance is 16% or less. If the scratch total light transmittance is too high, the vapor-deposited polypropylene film may not have sufficient scratch resistance and may have a poor appearance. If the scratch total light transmittance is 16% or less, it can be said that scratches on the vapor-deposited layer 60 caused by rubbing are suppressed, and therefore the deterioration of the design of the film caused by rubbing between the films during transportation and processing can be suppressed.
[0087] In addition, the vapor-deposited polypropylene film 50 preferably has a glossiness of 720% or more as measured in accordance with JIS Z 8741 (1997). By providing the vapor-deposited polypropylene film 50 with a good glossiness while maintaining a certain level of scratch resistance, the vapor-deposited polypropylene film can have an even more luxurious appearance.
[0088] In addition, in the vapor-deposited polypropylene film 50, the base film for vapor deposition on which the vapor-deposited layer 60 is formed is not particularly limited as long as it satisfies the scratch resistance values shown in formulas (iii) to (iv). As the base film for vapor deposition, it is preferable to use the polypropylene film 10 of the present invention shown in the embodiment. Since the polypropylene film 10 is suppressed in scratching of the first surface layer 20 having the vapor-deposited surface 21, deterioration of the appearance when the vapor-deposited polypropylene film 50 is formed by performing vapor deposition processing or the like can be suppressed.
[0089] 3, the vapor-deposited polypropylene film 50 may be laminated with at least one layer of lamination base film 110 on the vapor-deposited layer 60 side to form a laminated film 100. In the illustrated laminated film 100, the polypropylene film 10 has a two-layer structure consisting of a first surface layer 20 and a second surface layer 30. As described above, the polypropylene film 10 may have a three or more layer structure including an intermediate layer, etc.
[0090] The lamination base film 110 is preferably a film made of any one of a polyester film, a polyamide film, and a polypropylene film. Examples of polyester films include biaxially oriented polyethylene terephthalate films, polyamide films include biaxially oriented polyamide films, and polypropylene films include biaxially oriented polypropylene films and uniaxially oriented polypropylene films. These films are excellent in strength and can be suitably used as the base film of the laminated film 100. Such a laminated film 100 can be made into a laminate film that suppresses deterioration of the deposition layer 60, and can be suitably used as various packaging bags and the like. EXAMPLES
[0091] [Preparation of polypropylene film] In producing the polypropylene films of the prototypes 1 to 33, the materials described below were mixed and melted based on a predetermined mixing ratio (weight %), co-extruded by the T-die method, cooled with a cooling roll, and then subjected to a corona discharge treatment on the first surface layer to produce an unstretched polypropylene film. The films of the prototypes 1, 4, 5, and 30 were two-layer films consisting of a first surface layer (vapor deposition surface) and a second surface layer (heat seal surface), while the films of the prototypes 2, 3, 6 to 29, and 31 to 33 were three-layer films consisting of a first surface layer (vapor deposition surface), an intermediate layer, and a second surface layer (heat seal surface). The thickness of the films of the prototypes 1 to 33 was 25 μm. The materials used in each layer of the prototypes 1 to 33 are shown in Tables 1 to 5 below.
[0092] [Materials used] The following resins and anti-blocking agents were used for each layer. The melt flow rate (MFR) of each resin material conforms to JIS K 7210 (2014), and is measured at a test temperature of 230°C for polypropylene resin and 190°C for polyethylene resin.
[0093] The pore volume of the antiblocking agent was determined by the nitrogen adsorption method as follows. As a pretreatment, the antiblocking agent was subjected to vacuum degassing and drying at 200°C for 2 hours, and the nitrogen adsorption amount was measured and converted into the volume of liquid nitrogen for calculation. The nitrogen adsorption amount was measured using an automatic specific surface area / pore distribution measurement device (BELSORP-miniII, manufactured by Microtrack-Bell Co., Ltd.). The nitrogen adsorption amount (V) at a relative pressure of 0.990 was calculated by applying Gurvitsch's law to the obtained nitrogen adsorption amount and converting it into the volume of liquid nitrogen (V p In formula (v), M g is the molecular weight of the adsorbate (nitrogen: 28.020), ρ g (g / cm 3 ) is the density of the adsorbate (nitrogen: 0.808).
[0094]
number
[0095] [Resin material] PP1: Propylene-ethylene-butene random copolymer, melting point 139℃, MFR (230℃, 2.16kg): 7g / 10min PP2: Propylene-ethylene-butene random copolymer, melting point 142℃, MFR(230℃, 2.16kg):7g / 10min PP3: Propylene-ethylene random copolymer, melting point 135℃, MFR (230℃, 2.16kg): 7g / 10min PP4: Propylene-ethylene random copolymer, melting point 125℃, MFR (230℃, 2.16kg): 7g / 10min PP5: Propylene-ethylene random copolymer, melting point 147℃, MFR (230℃, 2.16kg): 7g / 10min PP6: Propylene homopolymer, melting point 164℃, MFR (230℃, 2.16kg): 7.5g / 10min PP7: Propylene homopolymer, melting point 166℃, MFR (230℃, 2.16kg): 7.5g / 10min PE1: High density polyethylene, melting point 134℃, MFR(190℃, 2.16kg):13g / 10min
[0096] [Anti-blocking agent (AB agent)] AB1: Amorphous silica, average particle size 3.9μm, pore volume 0.80ml / g AB2: Amorphous silica, average particle size 4.1μm, pore volume 1.25ml / g AB3: Regular silica, average particle size 2.7μm, pore volume 0.57ml / g AB4: Amorphous silica, average particle size 3.7μm, pore volume 1.00ml / g
[0097] [Prototype 1] Prototype example 1 is a polypropylene film whose first surface layer is made of 98.37 wt% PP1, 1.50 wt% PE1, 0.06 wt% AB1, and 0.07 wt% AB3, and whose second surface layer is made of 97.80 wt% PP4, 2.00 wt% PE1, 0.15 wt% AB2, and 0.05 wt% AB3, with a layer ratio of first surface layer:second surface layer = 4:1.
[0098] [Prototype 2] Prototype example 2 is a polypropylene film in which the composition of materials used for the first and second surface layers is the same as that of prototype example 1, and the intermediate layer is made of 30% by weight PP1, 30% by weight PP5, and 40% by weight PP7, with a layer ratio of first surface layer:intermediate layer:second surface layer = 1:3:1.
[0099] [Prototype 3] Prototype 3 is a polypropylene film in which the composition of materials used for the first surface layer, intermediate layer, and second surface layer is the same as that of Prototype 2, with a layer ratio of first surface layer:intermediate layer:second surface layer=1:6:1.
[0100] [Prototype 4] Prototype example 4 is a polypropylene film in which the first surface layer is made of 98.45% by weight PP2, 1.50% by weight PE1, and 0.05% by weight AB1, and the second surface layer is made of 98.40% by weight PP2, 1.50% by weight PE1, and 0.10% by weight AB1, with a layer ratio of first surface layer:second surface layer = 5:1.
[0101] [Prototype 5] Prototype 5 is a polypropylene film having the same composition as Prototype 4, except that the composition of the materials used in Prototype 4 was changed to 98.40% by weight of PP2 and 0.10% by weight of AB1 in the first surface layer.
[0102] [Prototype 6] Prototype example 6 is a polypropylene film in which the composition of materials used for the first and second surface layers is the same as that of prototype example 5, the intermediate layer is made of 60% by weight PP2 and 40% by weight PP7, and the layer ratio is first surface layer:intermediate layer:second surface layer = 1:4:1.
[0103] [Prototype 7] Prototype 7 is a polypropylene film having the same composition as Prototype 6, except that the composition of the materials used in Prototype 6 was changed to 98.20% by weight of PP2 and 0.30% by weight of AB1 in the first surface layer.
[0104] [Prototype 8] Sample 8 is a polypropylene film having the same structure as Sample 6, except that the antiblocking agent in the second surface layer was changed from AB1 to AB2 in the composition of the materials used in Sample 6.
[0105] [Prototype 9] Prototype 9 is a polypropylene film having the same composition as Prototype 7, except that the composition of the materials used in Prototype 7 was changed so that the second surface layer contained PP2 at 98.30% by weight and AB1 at 0.20% by weight.
[0106] [Prototype 10] Sample 10 is a polypropylene film having the same structure as Sample 6, except that the antiblocking agent in the second surface layer was changed from AB1 to AB4 in the composition of the materials used in Sample 6.
[0107] [Prototype example 11] Prototype 11 is a polypropylene film having the same composition as Prototype 10, except that the composition of the materials used in Prototype 10 was changed to 98.20% by weight of PP2 and 0.30% by weight of AB1 in the first surface layer.
[0108] [Prototype 12] Sample 12 is a polypropylene film having the same structure as Sample 10, except that the antiblocking agent in the first surface layer was changed from AB1 to AB2 in the composition of the materials used in Sample 10.
[0109] [Prototype 13] Prototype 13 is a polypropylene film having the same composition as Prototype 6, except that the composition of the materials used in the first surface layer was changed to 97.90% by weight of PP2 and 0.60% by weight of AB1.
[0110] [Prototype 14] Prototype 14 is a polypropylene film having the same composition as Prototype 13, except that the composition of the materials used in Prototype 13 was changed to 98.30% by weight of PP2 and 0.20% by weight of AB1 in the second surface layer.
[0111] [Prototype 15] Prototype 15 is a polypropylene film having the same composition as Prototype 13, except that the composition of the materials used in Prototype 13 was changed to 98.20% by weight of PP2 and 0.30% by weight of AB1 in the second surface layer.
[0112] [Prototype 16] Sample 16 is a polypropylene film having the same structure as Sample 6, except that the antiblocking agent in the first surface layer was changed from AB1 to AB2 in the composition of the materials used in Sample 6.
[0113] [Prototype 17] Sample 17 is a polypropylene film having the same structure as Sample 10, except that the antiblocking agent in the first surface layer was changed from AB1 to AB4 in the composition of the materials used in Sample 10.
[0114] [Prototype 18] Sample 18 is a polypropylene film having the same structure as Sample 17, except that the antiblocking agent in the second surface layer was changed from AB4 to AB1 in the composition of the materials used in Sample 17.
[0115] [Prototype Example 19] Prototype 19 is a polypropylene film with the same composition as Prototype 18, except that the first surface layer contained 98.35% by weight of PP2 and 0.15% by weight of AB4 compared to the composition of the materials used in Prototype 18.
[0116] [Prototype Example 20] Prototype 20 is a polypropylene film with the same composition as Prototype 18, except that the composition of the materials used in Prototype 18 was changed to 98.20 wt % PP2 and 0.30 wt % AB4 in the first surface layer.
[0117] [Prototype Example 21] Prototype 21 is a polypropylene film with the same composition as Prototype 6, except that the polypropylene resin for the first surface layer was changed to 73.37% by weight of PP2 and 25.00% by weight of PP6, and the anti-blocking agents were changed to 0.10% by weight of AB1 and 0.03% by weight of AB3.
[0118] [Prototype Example 22] Prototype Example 22 is a polypropylene film with the same composition as Prototype Example 21, except that the composition of the materials used in Prototype Example 21 was changed to 23.32 wt% PP2, 75.00 wt% PP6, and 0.08 wt% AB3 in the first surface layer.
[0119] [Prototype Example 23] Prototype Example 23 is a polypropylene film with the same composition as Prototype Example 21, except that the composition of the materials used in Prototype Example 21 was changed to 98.30 wt% PP6 (0.00 wt% PP2) and 0.10 wt% AB3 in the first surface layer.
[0120] [Prototype Example 24] Prototype 24 is a polypropylene film with the same composition as Prototype 6, except that the polypropylene resin in the first surface layer was changed to 68.40% by weight of PP2 and 30.00% by weight of PP3 compared to the composition of the materials used in Prototype 6.
[0121] [Prototype Example 25] Prototype 25 is a polypropylene film having the same composition as Prototype 24, except that the composition of the materials used in Prototype 24 was changed to 28.40% by weight of PP2 and 70.00% by weight of PP3 in the first surface layer.
[0122] [Prototype Example 26] Prototype 26 is a polypropylene film with the same composition as Prototype 24, except that the PP3 in the first surface layer was changed to 98.40% by weight (PP2 was 0.00% by weight) in the composition of the materials used in Prototype 24.
[0123] [Prototype Example 27] Prototype 27 is a polypropylene film with the same composition as Prototype 6, except that the second surface layer contained 98.35% by weight of PP2 and 0.15% by weight of AB1 compared to the composition of the materials used in Prototype 6.
[0124] [Prototype Example 28] Prototype 28 is a polypropylene film with the same composition as Prototype 7, except that the composition of the materials used in Prototype 7 was changed so that the second surface layer contained PP2 at 98.20% by weight and AB1 at 0.30% by weight.
[0125] [Prototype Example 29] Prototype 29 is a polypropylene film with the same composition as Prototype 16, except that the composition of the materials used in Prototype 16 was changed to 98.35% by weight of PP2 and 0.15% by weight of AB1 in the second surface layer.
[0126] [Prototype Example 30] Prototype 30 is a polypropylene film having the same composition as Prototype 4, except that the composition of the materials used in Prototype 4 was changed to 98.35% by weight of PP2 and 0.15% by weight of AB1 in the second surface layer.
[0127] [Prototype Example 31] Prototype 31 is a polypropylene film having the same composition as Prototype 18, except that the composition of the materials used in Prototype 18 was changed to 98.30% by weight of PP2 and 0.20% by weight of AB1 in the second surface layer.
[0128] [Prototype Example 32] Sample 32 is a polypropylene film having the same structure as Sample 31, except that the antiblocking agent in the first surface layer was changed from AB4 to AB2 in the composition of the materials used in Sample 31.
[0129] [Prototype Example 33] Sample 33 is a polypropylene film having the same structure as Sample 31, except that in the composition of the materials used in Sample 31, the antiblocking agent in the first surface layer was changed from AB4 to AB1.
[0130] [Table 1]
[0131] [Table 2]
[0132] [Table 3]
[0133] [Table 4]
[0134] [Table 5]
[0135] Regarding the evaluation of the polypropylene films of the prototypes 1 to 33, the arithmetic mean roughness SRa1 (μm) of the three-dimensional surface roughness of the first surface layer, the number of peaks SPc2 (number) having a height of 1 μm or more in the three-dimensional surface roughness of the second surface layer, the pore volume V2 (ml / g) of the antiblocking agent contained in the second surface layer obtained by the nitrogen adsorption method, the scratch haze (%), and the gloss (%) were measured. In addition, the scratch resistance 1 (formula (i)) was calculated based on the measurement results of the arithmetic mean roughness of the first surface layer and the number of peaks having a height of 1 μm or more in the second surface layer, and the scratch resistance 2 (formula (ii)) was calculated using the pore volume V2 (ml / g) of the antiblocking agent contained in the second surface layer obtained by the nitrogen adsorption method. In addition, when a plurality of antiblocking agents are contained in the second surface layer, the pore volume of the antiblocking agent was calculated based on the content ratio of each antiblocking agent to the content of the total antiblocking agent. The results of each measurement and the evaluation thereof are shown in Tables 6 to 10 described later.
[0136] [Measurement of three-dimensional surface roughness] The arithmetic mean roughness (SRa1) of the three-dimensional surface roughness of the first surface layer and the number of peaks with a height of 1 μm or more (SPc2) of the three-dimensional surface roughness of the second surface layer were measured under the following measurement conditions using a three-dimensional surface roughness measuring device "SE3500K (manufactured by Kosaka Laboratory Co., Ltd.)" and an analyzer "TDA-22 (manufactured by Kosaka Laboratory Co., Ltd.)". The measurement standards for each roughness (SRa1, SPc2) were referenced to JIS B 0601. Measurement direction: MD X measurement length: 2mm X-feed pitch: 4μm X-feed speed: 0.2mm / s Y measurement length: 0.25mm Y feed pitch: 5μm Z magnification: 20000 Polarity: Positive Leveling: Least Squares Method Low cutoff: 0.250mm High cutoff: 0.000mm Phase characteristic: Gaussian Number of Y lines: 51 Detector: PU-DJ2S Stylus tip radius: 2μm Stylus apex angle: 60° Measuring force: 0.7mN or less Particle Analysis: Particle Analysis (Multiple Levels) Output content setting: Mountain particle numerical output Hysteresis width: 0μm Slice level interval: 0.1μm
[0137] [Calculation of scratch resistance] The value of scratch resistance 1 was calculated based on formula (i) using the arithmetic mean roughness (SRa1) of the three-dimensional surface roughness of the first surface layer and the number of peaks with a height of 1 μm or more (SPc2) of the three-dimensional surface roughness of the second surface layer, which were obtained by measuring the three-dimensional surface roughness. In addition, the value of scratch resistance 2 was calculated based on formula (ii) using the arithmetic mean roughness (SRa1) of the three-dimensional surface roughness of the first surface layer, the number of peaks with a height of 1 μm or more (SPc2) of the three-dimensional surface roughness of the second surface layer, and the pore volume (V2) of the antiblocking agent contained in the second surface layer.
[0138] [Scratch haze measurement] The haze (%) of the film before rubbing was measured using a haze meter "NDH-8000 (manufactured by Nippon Denshoku Industries Co., Ltd.)" in accordance with JIS K 7136 (2000). Next, three test pieces were prepared for each prototype, and a friction tester "FRICTION TESTER TR (manufactured by Toyo Seiki Seisakusho Co., Ltd.)" was used to place the second surface layer of the test piece on the test table side and the first surface layer on the sliding piece side, referring to JIS K 7125 (1999), and the sliding piece was slid once to rub the first surface layer and the second surface layer together. The conditions were as follows. Material of the bottom of the slide: Rubber Test speed: 100mm / min Travel distance: 80mm Total mass of the slider: 2.17kg
[0139] Next, the haze of the film on the sliding side that was rubbed together was measured at six points, and the maximum value (maximum haze) was read. Here, the haze of the film measured before rubbing was defined as H1 (%), and the average value of the maximum haze of the three test pieces after rubbing was defined as H2 (%), and the scratch haze (ΔH = H2 - H1) was calculated. The obtained scratch haze value was evaluated as "Excellent (◎)" when it was 6.5% or less, "Good (○)" when it was 10% or less, and "Unacceptable (×)" when it was more than 10%.
[0140] [Gloss measurement] The glossiness (%) was measured in accordance with JIS Z 8741 using a glossmeter "VG-7000 (manufactured by Nippon Denshoku Industries Co., Ltd.)" at a measurement angle of 60° and in the machine direction (MD) of the film. A glossiness measurement result of 110% or more was evaluated as "excellent (◎)", a glossiness measurement result of 100% or more but less than 110% was evaluated as "fair (○)", and a glossiness measurement result of less than 100% was evaluated as "poor (×)".
[0141] [Table 6]
[0142] [Table 7]
[0143] [Table 8]
[0144] [Table 9]
[0145] [Table 10]
[0146] [Results and Discussion (1)] As can be seen from Tables 6 to 10, among the polypropylene films of Prototype Examples 1 to 33, the films of Prototype Examples 1 to 26 had good scratch haze, but the films of Prototype Examples 27 to 33 had poor scratch haze.
[0147] In the prototypes 1 to 26, which had good scratch haze, the arithmetic mean roughness (SRa1) of the first surface layer was 0.027 to 0.070 μm, the number of peaks (SPc2) of 1 μm or more in the second surface layer was 8 to 117, and the pore volume (V2) of the antiblocking agent (hereinafter, AB agent) in the second surface layer was 0.80 to 1.25 ml / g. On the other hand, in the prototypes 27 to 33, which did not have good scratch haze, the arithmetic mean roughness (SRa1) of the first surface layer was 0.027 to 0.046 μm, the number of peaks (SPc2) of 1 μm or more in the second surface layer was 64 to 117, and the pore volume (V2) of the AB agent in the second surface layer was 0.80 ml / g, all of which were within the numerical ranges in which the respective physical properties of the prototypes 1 to 26 were measured. Therefore, it is considered difficult to individually specify preferable conditions for the physical properties of the film.
[0148] Therefore, when the value of scratch resistance 1 (SPc2 / SRa1) expressed based on the arithmetic mean roughness (SRa1) of the first surface layer and the number of peaks of 1 μm or more (SPc2) of the second surface layer was examined, the scratch resistance 1 values of prototypes 1 to 26 were 186 to 1671. In contrast, the scratch resistance 1 values of prototypes 27 to 33 were 2133 to 3407, all of which were higher than those of prototypes 1 to 26. Thus, it can be said that the physical property of the film expressed by (SPc2 / SRa1) is effective as an index of the scratch resistance of the film. And, from the results of prototypes 1 to 26 and prototypes 27 to 33, it is considered that the preferable relationship for scratch resistance is (SPc2 / SRa1)≦2100.
[0149] Next, the value of scratch resistance 2 {(SPc2 / V2) / SRa1} expressed based on the arithmetic mean roughness (SRa1) of the first surface layer, the number of peaks of 1 μm or more of the second surface layer (SPc2), and the pore volume (V2) of the AB agent was examined. In prototypes 1 to 26, the value of {(SPc2 / V2) / SRa1} was 172 to 2527. In contrast, in prototypes 27 to 33, the value of {(SPc2 / V2) / SRa1} was 2667 to 4259, all of which were values higher than those of prototypes 1 to 26. It can be said that the physical property of the film expressed by {(SPc2 / V2) / SRa1} is effective as an index of the scratch resistance of the film. From the results of Samples 1 to 26 and Samples 27 to 33, it is considered that the preferable relationship for scratch resistance is {(SPc2 / V2) / SRa1}≦2600.
[0150] Furthermore, among prototypes 1 to 26, which had good scratch haze, prototypes 13 to 15 had slightly insufficient gloss. Comparing prototypes 13 to 15 with the other prototypes, the arithmetic mean roughness (SRa1) of the first surface layer was higher than that of the other prototypes. If the arithmetic mean roughness (SRa1) of the first surface layer is too high, the gloss may be deteriorated. From the viewpoint of obtaining good gloss, it is considered that the preferable arithmetic mean roughness (SRa1) of the first surface layer is about 0.060 or less.
[0151] As described above, in the polypropylene film of the present invention, the scratch haze is good when the scratch resistance 1 represented by (SPc2 / SRa1) is 2100 or less. In addition, the scratch haze is good when the scratch resistance 2 represented by {(SPc2 / V2) / SRa1} is 2600 or less. In particular, as can be seen from each prototype, it is difficult to specify conditions under which good scratch resistance can be obtained from the individual physical properties of the film, and therefore, it can be said that the significance of using the relationship between specific physical properties of the film as an index of scratch resistance performance is also shown.
[0152] [Preparation of vapor-deposited polypropylene film] For the polypropylene films of the prototypes 1, 2, and 4 to 33, deposition processing was performed on the first surface layer to produce a deposition polypropylene film. In the deposition processing, aluminum was deposited on each polypropylene film using a resistance heating vacuum deposition device (manufactured by Machine Technology Co., Ltd.) so that the aluminum deposition film thickness was 350 Å and the vacuum degree was 9E-03 Pa. Regarding the evaluation of the aluminum deposition polypropylene films of the prototypes 1, 2, and 4 to 33 obtained, the arithmetic mean height Sa1 (μm) of the deposition layer, the scratch total light transmittance (%), and the gloss (%) were measured. In addition, the scratch resistance 3 and 4 were calculated based on the measurement results of the pore volume of the antiblocking agent of the second surface layer, the number of peaks of the second surface layer with a peak height of 1 μm or more, and the measurement results of the arithmetic mean height of the deposition layer. The results of each measurement and the evaluation are shown in Tables 11 to 15 described later.
[0153] [Measurement of the arithmetic mean height of the deposition layer] The arithmetic mean height (Sa1) of the deposition layer was measured using a laser microscope "VK-X 3000 (manufactured by Keyence Corporation)" under the following measurement conditions. <Measurement> Shape measurement: Top surface measurement Scan mode: Laser confocal <Analysis> Surface shape correction: Waviness removal Measurement: Surface roughness measurement Measurement area: All areas Filter: Gaussian S-Filter: None F-Operation: None L-Filter: None End effect compensation: ON
[0154] [Calculation of scratch resistance of vapor-deposited polypropylene film] The scratch resistance 3 was calculated based on formula (iii) using the arithmetic mean height (Sa1) of the deposition layer and the number of peaks in the three-dimensional surface roughness of the second surface layer that are 1 μm or more in height (SPc2) measured by the laser scope. The scratch resistance 4 was calculated based on formula (iv) using the arithmetic mean height (Sa1) of the deposition layer, the number of peaks in the three-dimensional surface roughness of the second surface layer that are 1 μm or more in height (SPc2), and the pore volume (V2) of the antiblocking agent contained in the second surface layer.
[0155] [Measurement of total light transmittance from scratches] The total light transmittance (%) of the vapor-deposited polypropylene film before rubbing was measured using a haze meter "NDH-8000 (manufactured by Nippon Denshoku Industries Co., Ltd.)". Next, three test pieces were prepared for each prototype, and a friction tester "FRICTION TESTER TR (manufactured by Toyo Seiki Seisakusho Co., Ltd.)" was used to place the second surface layer of the test piece on the test table side and the vapor-deposited layer on the sliding side, referring to JIS K 7125 (1999). The sliding piece was slid once to rub the vapor-deposited layer against the second surface layer. The conditions were as follows. Material of the bottom of the slide: Rubber Test speed: 100mm / min Travel distance: 80mm Total mass of the slider: 2.17kg
[0156] Next, the total light transmittance of the vapor-deposited polypropylene film on the sliding side that was rubbed together was measured at six points, and the maximum value (maximum total light transmittance) was read. Here, the total light transmittance of the vapor-deposited polypropylene film measured before rubbing was defined as T1 (%), and the average of the maximum total light transmittances of the three test pieces after rubbing was defined as T2 (%), and the scratch total light transmittance (ΔT = T2 - T1) was calculated. The obtained scratch total light transmittance value of 16% or less was evaluated as "Excellent (◎)", and the value of more than 16% was evaluated as "Poor (×)".
[0157] [Measurement of gloss of vapor-deposited polypropylene film] The glossiness (%) was measured using a glossmeter "VG-7000 (manufactured by Nippon Denshoku Industries Co., Ltd.)" at a measurement angle of 60° and in the machine direction (MD) of the film. A glossiness measurement result of 720% or more was rated as "Excellent (◎)", a glossiness measurement result of 700% or more but less than 720% was rated as "Fair (○)", and a glossiness measurement result of less than 700% was rated as "Poor (×)".
[0158] [Table 11]
[0159] [Table 12]
[0160] [Table 13]
[0161] [Table 14]
[0162] [Table 15]
[0163] [Results and Discussion (2)] As can be seen from Tables 11 to 15, for the vapor-deposited polypropylene films of prototypes 1, 2, 4 to 33, the total scratch light transmittance of the films of prototypes 1, 2, 4 to 8, 10 to 14, and 16 to 26 was good, but the total scratch light transmittance of the films of prototypes 9, 15, and 27 to 33 was poor.
[0164] In the prototypes 1, 2, 4-8, 10-14, and 16-26, which had good scratch total light transmittance, the arithmetic mean height (Sa1) of the first surface layer was 0.37-0.72 μm, the number of peaks of 1 μm or more in the second surface layer (SPc2) was 8-117, and the pore volume (V2) of the AB agent in the second surface layer was 0.80-1.25 ml / g. On the other hand, in the prototypes 9, 15, and 27-33, which did not have good scratch total light transmittance, the arithmetic mean height (Sa1) of the first surface layer was 0.037-0.046 μm, the number of peaks of 1 μm or more in the second surface layer (SPc2) was 64-117, and the pore volume (V2) of the AB agent in the second surface layer was 0.80 ml / g, all of which were within the range of values measured for each physical property of the prototypes 1, 2, 4-8, 10-14, and 16-26.
[0165] Then, the value of scratch resistance 3 (SPc2 / Sa1) expressed based on the arithmetic mean height (Sa1) of the deposition layer and the number of peaks of 1 μm or more in the second surface layer (SPc2) was examined. The scratch resistance 3 values of prototypes 1, 2, 4-8, 10-14, and 16-26 were 13-128. In contrast, the scratch resistance 3 values of prototypes 9, 15, and 27-33 were 136-221, all of which were higher than those of prototypes 1, 2, 4-8, 10-14, and 16-26. It can be said that the physical property of the film expressed by (SPc2 / Sa1) is effective as an index of the scratch resistance of the film. From the results of Test Examples 1, 2, 4 to 8, 10 to 14, 16 to 26 and Test Examples 9, 15, 27 to 33, it is considered that the preferable relationship for scratch resistance is (SPc2 / Sa1)≦130.
[0166] Next, the value of scratch resistance 4 {(SPc2 / V2) / Sa1} expressed based on the arithmetic mean height (Sa1) of the vapor-deposited layer, the number of peaks of 1 μm or more in the second surface layer (SPc2), and the pore volume (V2) of the AB agent was examined. In the prototypes 1, 2, 4-8, 10-14, and 16-26, the scratch resistance 4 values were 12-160. In contrast, the scratch resistance 4 values in the prototypes 9, 15, and 27-33 were 170-276, all of which were higher than those in the prototypes 1, 2, 4-8, 10-14, and 16-26. It can be said that the physical property of the vapor-deposited film expressed by {(SPc2 / V2) / Sa1} is effective as an index of the scratch resistance of the film. From the results of Prototype Examples 1, 2, 4 to 8, 10 to 14, 16 to 26 and Prototype Examples 9, 15, 27 to 33, it is considered that the preferable relationship for the scratch resistance of a vapor-deposited film is {(SPc2 / V2) / Sa1}≦165.
[0167] Furthermore, among prototypes 1, 2, 4-8, 10-14, and 16-26, which had good scratch total light transmittance, prototypes 13 and 14 had slightly insufficient gloss. Comparing prototypes 13 and 14 with the other prototypes, the arithmetic mean height (Sa1) of the first surface layer was higher than the other prototypes. If the arithmetic mean height (Sa1) of the first surface layer is too high, the gloss may be deteriorated. From the viewpoint of obtaining good gloss, it is considered that the preferable arithmetic mean height (Sa1) of the first surface layer is about 0.70 or less.
[0168] As described above, in the vapor-deposited polypropylene film of the present invention, the scratch total light transmittance is good when the scratch resistance 3 represented by (SPc2 / Sa1) is 130 or less. In addition, the scratch total light transmittance is good when the scratch resistance 4 represented by {(SPc2 / V2) / Sa1} is 165 or less. In addition, as in the polypropylene film of the present invention, it is difficult to specify conditions under which good scratch resistance can be obtained from the individual physical properties of the film in the vapor-deposited polypropylene film, so that the significance of using the relationship between specific physical properties of the film as an index of scratch resistance performance is also shown.
[0169] [Making laminated film] Laminated films were produced for the aluminum-deposited polypropylene films of Samples 1, 2, 4-8, 10-14, and 16-26. The laminated films were produced by applying a two-component curing polyester adhesive at a rate of approximately 4 g / m2 to the corona-treated surface of a polyester film (FE2001#12 manufactured by Futamura Chemical Co., Ltd.). 2 The laminated film was then coated with a coating of the aluminum vapor deposition material and attached to the aluminum vapor deposition surface of each prototype by dry lamination. The appearance of each of the resulting laminated films was visually inspected and found to be in good condition with no wrinkles or the like.
[0170] As shown and described above, the polypropylene film of the present invention can have excellent scratch resistance by satisfying that the scratch resistance value calculated from the arithmetic mean roughness (SRa1) (μm) of the three-dimensional surface roughness of the first surface layer is 2100 or less. In addition, the polypropylene film of the present invention can have even better scratch resistance by further satisfying that the scratch resistance value calculated from the arithmetic mean roughness (SRa1) (μm) of the three-dimensional surface roughness of the first surface layer, the number of peaks (SPc2) (pieces) with a peak height of 1 μm or more in the three-dimensional surface roughness of the second surface layer, and the pore volume (V2) (ml / g) of the antiblocking agent contained in the second surface layer is 2600 or less. Therefore, even if the first surface layer and the second surface layer are rubbed against each other by winding or the like, scratches on the surface of the first surface layer are suppressed, and surface treatment such as deposition processing can be appropriately performed. Therefore, the polypropylene film of the present invention can be suitably used as a substrate film for deposition.
[0171] The vapor-deposited polypropylene film of the present invention can have excellent scratch resistance by satisfying a scratch resistance value calculated from the arithmetic mean height (Sa1) (μm) of the vapor-deposited layer and the number of peaks (SPc2) (number) with a height of 1 μm or more in the three-dimensional surface roughness of the second surface layer of 130 or less. The vapor-deposited polypropylene film of the present invention can have even better scratch resistance by further satisfying a scratch resistance value calculated from the arithmetic mean height (Sa1) (μm) of the vapor-deposited layer, the number of peaks (SPc2) (number) with a height of 1 μm or more in the three-dimensional surface roughness of the second surface layer of 165 or less. Therefore, even if the vapor-deposited layer and the second surface layer are rubbed against each other by winding, etc., scratches on the surface of the vapor-deposited layer can be suppressed, and deterioration of the design of the film due to rubbing between the films can be suppressed. [Industrial Applicability]
[0172] As described above, the polypropylene film of the present invention has excellent scratch resistance on one of the film surfaces, which is the processed surface, and can be well subjected to deposition processing and printing processing. In addition, by suppressing the scratchability of the other surface of the processed surface, the scratch resistance of the film after processing can also be made good. Therefore, it is promising as a replacement for conventional base films for deposition and printing films. In addition, the vapor-deposited polypropylene film of the present invention has excellent scratch resistance on the vapor-deposited layer surface, and the scratchability of the other surface is suppressed, so that the deterioration of the design of the vapor-deposited film can be effectively suppressed. Therefore, by forming a laminate film using the vapor-deposited polypropylene film, it is possible to make a laminate film that can suppress the deterioration of the vapor-deposited layer, and it is promising as a replacement for laminate films used in various packaging bags, etc. [Explanation of symbols]
[0173] 10 Polypropylene film 20 First surface layer 21 Vapor deposition surface 30 Second surface layer 31 Heat seal surface 40 Middle Class 50 Vapor-deposited polypropylene film 60 Deposited layer 100 Laminated Film 110 Lamination base film
Claims
1. A polypropylene film consisting of at least two layers, a first surface layer and a second surface layer, both the first surface layer and the second surface layer contain an antiblocking agent; When the arithmetic mean roughness of the three-dimensional surface roughness of the first surface layer is SRa1 (μm) and the number of peaks having a height of 1 μm or more in the three-dimensional surface roughness of the second surface layer is SPc2 (pieces), the scratch resistance value represented by the following formula (i) is satisfied: A polypropylene film characterized by: [0010]
2. 2. The polypropylene film according to claim 1, wherein the antiblocking agent contained in the second surface layer has a pore volume V2 (ml / g) determined by a nitrogen adsorption method, and the polypropylene film satisfies the scratch resistance value represented by the following formula (ii): [0025]
3. 3. The polypropylene film according to claim 1, wherein the first surface layer is provided with a vapor-deposited layer by vapor deposition.
4. The polypropylene film according to claim 1 or 2, wherein the first surface layer has a gloss of 110% or more as measured in accordance with JIS Z 8741 (1997).
5. 3. The polypropylene film according to claim 1, wherein the first surface layer is subjected to a surface treatment.
6. The polypropylene film according to claim 1 or 2, which is a non-oriented film.
7. 3. The polypropylene film according to claim 1, wherein the antiblocking agent contained in the first surface layer has a pore volume of 0.5 to 1.3 ml / g as determined by a nitrogen adsorption method and an average particle diameter of 2.5 to 4.5 μm as measured by a laser diffraction method.
8. A vapor-deposited film comprising at least two layers, a first surface layer and a second surface layer, both of which contain an antiblocking agent, and a vapor-deposited layer formed on the first surface layer of a polypropylene film, When the arithmetic mean height of the deposition layer is Sa1 (μm) and the number of peaks having a peak height of 1 μm or more in the three-dimensional surface roughness of the second surface layer is SPc2 (pieces), the scratch resistance value represented by the following formula (iii) is satisfied:
1. A vapor-deposited polypropylene film. [0030]
9. 9. The vapor-deposited polypropylene film according to claim 8, which satisfies the scratch resistance value represented by the following formula (iv), when the pore volume of the antiblocking agent contained in the second surface layer, determined by a nitrogen adsorption method, is V2 (ml / g): [0045]
10. 10. The vapor-deposited polypropylene film according to claim 8, wherein the vapor-deposited layer has a gloss of 720% or more as measured in accordance with JIS Z 8741 (1997).
11. 10. The vapor-deposited polypropylene film according to claim 8, wherein the polypropylene film is a non-oriented film.
12. The vapor-deposited polypropylene film according to claim 8 or 9, wherein the antiblocking agent contained in the first surface layer has a pore volume of 0.5 to 1.3 ml / g as determined by a nitrogen adsorption method and an average particle diameter of 2.5 to 4.5 μm as measured by a laser diffraction method.
13. 10. A laminated film using the vapor-deposited polypropylene film according to claim 8 or 9, characterized in that at least one layer of a base film for lamination made of any one of a polyester-based film, a polyamide-based film, and a polypropylene-based film is laminated on the vapor-deposited layer side of the vapor-deposited polypropylene film.
Citation Information
Patent Citations
Polypropylene based oriented film
JP2006095954A
Film for packaging bag and packaging bag for vegetables and fruit
JP2020040361A
Polypropylene film, and vapor-deposited film and laminate film
JP2024089609A
Biaxially oriented polypropylene film, multilayered film including metal film, and film capacitor
WO2017077752A1
Polypropylene resin composition for metallized film, film and metallized film made thereof
JP2004076004A